Hubungan Tingkat Kecemasan dengan Akses Vaskular Cimino (Fistula Arteriovenosa) Pada Pasien Yang Menjalani Terapi Hemodialisa di RSU Royal Prima Medan Tahun 2024 - Agfornidar Zalukhu; Saniyyah Aribah Dhilla Br. Sitohang; Chelsea Paulina Duha; Wiajeng Mustikah; Juniati Simanjuntak; Karmila Br. Kaban (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: The kidneys may slowly and irreversibly suffer damage from chronic kidney disease (CKD). Polycystic kidney disease, diabetes mellitus, hypertension, glomerular inflammation, HIV/AIDS, and other medical disorders are common causes of this illness. The purpose of this study is to investigate the association between hemodialysis patients' anxiety levels and their CImino vascular access at Royal Prima Medan General Hospital. In 2024, hemodialysis patients at Royal Prima Medan General Hospital will be studied to see whether there is a correlation between anxiety levels and cimino vascular access. The study will use quantitative methodology and a cross-sectional analytic survey methodology. This study's sample was selected using an accidental sampling strategy, which involves selecting samples by random via chance encounters with researchers who might be good sources of information. To determine the link between several nominal and ordinal variables, bivariate analysis employs the Chi-Square test. Conclusion: Out of the total number of respondents, 28 had extremely long-term usage, with 5 having extremely long-term usage making up a minority. According to the data, which shows a substantial correlation between anxiety levels and cimino vascular access in hemodialysis patients (p < 0.05), we may reject H0 and embrace Ha. Recommendations: For Participants and Study Sites, For Future Scholars